Thermosolutal convection in a baffled curvilinear porous cabinet filled with magneto radiative hybrid nanofluid - Hansda, Samrat; Chattopadhyay, Anirban; Pandit, Swapan K.; Öztop, Hakan Fehmi (Nature Portfolio, 2025)
This study focuses on optimizing the thermosolutal performance of a wavy porous cabinet with a T-shaped cold baffle, highlighting the utilization of a radiative Cu-\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\hbox {Al}_{2}$$\end{document}\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\hbox {O}_{3}$$\end{document}-water hybrid nanoliquid and diverse heating strategies. The purpose of this work is to evaluate the influence of these factors on hydromagnetic thermosolutal behavior under the influence of various thermal boundary conditions. By employing an efficient Higher Order Compact (HOC) scheme, the Navier-Stokes equations in streamfunction (\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\psi$$\end{document})-vorticity (\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\zeta$$\end{document}) form and energy as well as species transport equations are solved. In a novel approach, the study introduces a T-shaped cold baffle in the middle of the container, introducing complexity to the porous configuration. The investigation encompasses three distinct heating scenarios: uniform heating and soluting of the lower border (Case-1), linear heating and soluting (Case-2), and non-uniform heating and soluting (Case-3), while maintaining the side walls at cold and low concentration. The upper wall remains adiabatic. The results reveal a significant improvement in energy transfer across all cases, with an increase of 467.12% for Case-1, 470.98% for Case-2, and 387.78% for Case-3 as the radiation parameter (\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$Rd$$\end{document}) is varied from 1 to 10. In contrast, solutal transfer experiences a slight decline, quantified as 3.09% for Case-1, 2.05% for Case-2, and 6.07% for Case-3. These findings emphasize the superior thermosolutal performance of Case-1, where an optimized heating strategy significantly enhances the overall system efficiency. This study provides valuable insights for improving thermal management systems in practical applications. Notably, in areas such as electronic device cooling, heat exchangers, and porous industrial processes, the findings offer the potential for enhanced efficiency and reliability.
Keywords: T-shaped baffle; Different heating strategy; Energy and solutes transfer; Hybrid nanofluid; Higher order compact scheme (HOC); Thermal radiation; Irreversibility